2017
DOI: 10.3747/co.24.3488
|View full text |Cite
|
Sign up to set email alerts
|

The Two Solitudes of Primary Care and Cancer Specialist Care: Is There a Bridge?

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…A number of qualitative 7 and intervention or disease cohort studies, including randomized trials 8 , have been carried out, but we found no population-based studies that identify the individuals who are and are not using navigation. Furthermore, the need for navigation might be changing, given the accelerating discovery of innovative cancer treatments, the fact that more people are living longer with cancer 9 , the current focus on narrowing the gap between oncology and primary care 10,11 , the aging of the population, and greater interest in advance care planning and a palliative approach to care [12][13][14] . Population-based surveillance of people with life-limiting conditions can provide evidence that will help in critically appraising established navigation programs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of qualitative 7 and intervention or disease cohort studies, including randomized trials 8 , have been carried out, but we found no population-based studies that identify the individuals who are and are not using navigation. Furthermore, the need for navigation might be changing, given the accelerating discovery of innovative cancer treatments, the fact that more people are living longer with cancer 9 , the current focus on narrowing the gap between oncology and primary care 10,11 , the aging of the population, and greater interest in advance care planning and a palliative approach to care [12][13][14] . Population-based surveillance of people with life-limiting conditions can provide evidence that will help in critically appraising established navigation programs.…”
Section: Introductionmentioning
confidence: 99%
“…These results are relevant in the context of bridging the "two soli tudes" of primary and specialist care. 4 Participant suggestions, namely the implementation of care pathways with further support for family physicians, are important, given the strong promotion of pathways in the Canadian context to guide care of patients with different can cer types. 17 A successful example is the Alberta Breast Cancer Diagnostic Assessment Pathway, which addresses variation and wait time between discovery of a highly suspicious finding on imaging and referral to a breast program.…”
Section: Suggestionsmentioning
confidence: 99%
“…1,2 In Canada, family physicians make important contributions to the care of people with can cer throughout the care continuum. 3,4 Academic discussions related to this topic have focused on providing clarity about the role of family physicians, and on identifying challenges pertaining to the provision of cancer care in the commun ity. 3,[5][6][7] However, the emphasis has been mainly on post diagnostic care, with a particular focus on transitions from specialty cancer care back to the community.…”
mentioning
confidence: 99%
“… 1 In periods with intensive treatment in hospital, it is often unclear to patients who will take care of their comorbidities and psychosocial aspects of living with a life-threatening disorder. 2 The integration of general practitioners (GPs) into survivorship care is needed and underpinned internationally. 3 However, GPs may feel insufficiently informed by specialists and thereby be left with an unclearly defined role.…”
Section: Introductionmentioning
confidence: 99%